2022
DOI: 10.3390/nu14040801
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Geriatric Nutritional Risk Index and Modified Creatinine Index Combination on Mortality in Hemodialysis Patients

Abstract: The prognostic impact of the combination of a geriatric nutritional risk index (GRNI) and modified creatinine index, both of which assess nutritious status in hemodialysis patients, has not yet been well investigated thus far. Patients receiving maintenance hemodialysis in our institutes between February 2011 and January 2017 were retrospectively included. The baseline GRNI and modified Creatinine index were calculated and the impact of their combination on 5-year all-cause mortality following the index hemodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
1
11
1
Order By: Relevance
“…Therefore, cardiovascular and infection-related mortality remain to be clarified. Fujioka et al investigated 183 patients on hemodialysis with a mean hemodialysis vintage of 97 months for 5.5 years [15]. The hemodialysis vintage and follow-up in their study are similar to those in our study.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Therefore, cardiovascular and infection-related mortality remain to be clarified. Fujioka et al investigated 183 patients on hemodialysis with a mean hemodialysis vintage of 97 months for 5.5 years [15]. The hemodialysis vintage and follow-up in their study are similar to those in our study.…”
Section: Discussionsupporting
confidence: 86%
“…The high GNRI + low mCI group tended to show a higher mortality rate than that in the low GNRI + high mCI group in our study, which was not observed in the two previous studies mentioned above [14,15]. This discrepancy between studies might have been due to differences in the management of volume control.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations